2016
DOI: 10.1128/aac.01137-16
|View full text |Cite
|
Sign up to set email alerts
|

Rifamycin Resistance in Clostridium difficile Is Generally Associated with a Low Fitness Burden

Abstract: We characterized clinically occurring and novel mutations in the ␤ subunit of RNA polymerase in Clostridium difficile (CdRpoB), conferring rifamycin (including rifaximin) resistance. The Arg 505 Lys substitution did not impose an in vitro fitness cost, which may be one reason for its dominance among rifamycin-resistant clinical isolates. These observations were supported through the structural modeling of CdRpoB. In general, most mutations lacked in vitro fitness costs, suggesting that rifamycin resistance may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…16 Resistance to rifamycin in C. difficile is usually associated with mutations in the rpoB gene, which typically confer cross-resistance to multiple members of the antibiotic class and, importantly, are associated with a low fitness burden, allowing the phenotype to be stably maintained in the bacterial population. 57…”
Section: Discussionmentioning
confidence: 99%
“…16 Resistance to rifamycin in C. difficile is usually associated with mutations in the rpoB gene, which typically confer cross-resistance to multiple members of the antibiotic class and, importantly, are associated with a low fitness burden, allowing the phenotype to be stably maintained in the bacterial population. 57…”
Section: Discussionmentioning
confidence: 99%
“…In accord with our data, previous studies with E. coli ( 9 ), Salmonella enterica ( 22 ) and M. tuberculosis ( 34 ) revealed high cost of the rpoB R529C substitution to culture growth. Notably, homologous Lys substitution in Clostridium difficile at the equivalent position did not affect the fitness, likely by preserving the Lys side chain salt bridge with RNA ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, it has been shown that these mutations do persist in vivo , in the clinical setting. 29 In the case of fidaxomicin during all of these trials, there was only one report of a strain with reduced susceptibility, which was isolated from a relapse patient during a clinical trial. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 In Neisseria meningitidis , different mutations within rpoB have been associated with a range of fitness costs, and it has been suggested that the impact on virulence is such that they are only very rarely seen in the clinical setting. 32 Conversely, a study of rpoB mutations conferring reduced susceptibility of C. difficile to rifamycin 29 found that the majority of mutations generated in that study lacked in vitro fitness costs. Among these was the Arg505Lys substitution, which was as virulent as the WT, providing a possible explanation for its dominance among rifamycin-resistant clinical isolates.…”
Section: Discussionmentioning
confidence: 99%